Current situation and identified problems of legal competence of school principals: on the example of Tashkent region - Yusupova Dilnoza Fayzullaevna (Zien Journals, 2022)
The article analyzes the foreign experience in the field of legal competence of school principals, the current state of the legal competence of school principals in the Fergana region. Also, based on the analysis of the appraisal indicators, the initial problems were identified and scientific hypotheses about the development of the legal competence of school principals were developed.
Keywords: Legal knowledge; legal literacy; legal culture; healthy environment